Decreased synaptic proteins in neuronal exosomes of frontotemporal dementia and Alzheimer's disease. Issue 12 (6th September 2016) - Goetzl, Edward J.; Kapogiannis, Dimitrios; Schwartz, Janice B.; Lobach, Iryna V.; Goetzl, Laura; Abner, Erin L.; Jicha, Gregory A.; Karydas, Anna M.; Boxer, Adam; Miller, Bruce L.
ABSTRACT: Synaptic dysfunction occurs early in senile dementias, presumably as a result of decreased levels of functional synaptic proteins as found in autopsied brains of patients with Alzheimer's disease (AD) or frontotemporal dementia (FTD). Plasma neuronal‐derived exosomes (NDEs) were recovered by precipitation and immunoabsorption from 12 patients with AD, 16 with FTD, and 28 controls in a cross‐sectional study, and from 9 patients with AD, 10with FTD, and 19 controls in a longitudinal study. Six synaptic proteins in NDE extracts were quantified by ELISAs and normalized for exosome amounts. NDE levels of synaptophysin, synaptopodin, synaptotagmin‐2, and neurogranin were significantly lower in patients with FTD and ADthan in controls, but those of growth‐associated protein 43 and synapsin 1 were reduced only in patients with AD. Functionally relevant phosphorylation of synapsin 1 serine 9 was reduced in patients with FTD and AD, although total synapsin 1 protein was higher in FTD than in controls. NDE levels of synaptotagmin, synaptophysin, and neurograninwere decreased yearsbeforedementia inpatientswithFTD and AD.NDElevelsof synaptopodin, synaptotagmin, and synaptophysin, but not of amyloid β‐peptide 42 or P‐T181‐tau, were correlated significantly with cognition assessed bymini‐mental state examination or AD assessment scale‐cognitive subscale. NDE synaptic proteins may be useful preclinical indices and progression measures in senile dementias.—Goetzl, E. J., Kapogiannis, D., Schwartz, J. B., Lobach, I. V., Goetzl, L., Abner, E. L., Jicha, G. A., Karydas, A.M., Boxer, A., Miller, B. L. Decreased synaptic proteins in neuronal exosomes of frontotemporal dementia and Alzheimer's disease. FASEB J. 30, 4141–4148 (2016). www.fasebj.org